Journey to the East: a study of Ghanaian migrants in Guangzhou, China - Obeng, M.K.M. (Canadian Journal of African Studies, 2018)
In the late 1990s and early 2000s, nationals of sub-Saharan Africa who had initially settled in the Middle East and other parts of Southeast Asia moved in unprecedented numbers to Guangzhou, China in response to the 1997/8 Asian financial crisis. They were later joined by many more as the Chinese economy improved and the economic relationship between China and Africa strengthened. This paper discusses the experiences of identifiable sets of Ghanaian actors in Guangzhou, China in the last two decades. It outlines their respective characteristics, main activities, migratory trajectories and their motivations for traveling to China. The paper also analyzes their coping mechanisms in this relatively new destination and concludes that despite the current turbulence that characterizes the stay of Africans in China, the future of the Ghanaian community, and largely, Africans in China is bright.
Keywords: Africans in China; Migration; Ghana; China; Guangzhou